Active video games as an exercise tool for children with cystic fibrosis. - Hussey, Juliette; Forde, Cuisle; Greally, Peter (My University, 2013)
Background: Active video games are used in many hospitals as exercise tools for children with cystic fibrosis. However, the exercise intensity associated with playing these games has not been examined in this population. Methods: Children with cystic fibrosis [n = 30, aged 12.3 (2.6) years, 17 boys, BMI 17.7 (2.8) kg/m2] were recruited from outpatient clinics in Dublin hospitals. Age and gender matched control children were recruited from local schools. Oxygen consumption, metabolic equivalents (METs) calculated from resting O2, and heart rate were measured while playing Nintendo Wii™ (Nintendo Co. Ltd., Tokyo, Japan) Sports Boxing and Nintendo Wii Fit Free Jogging using a portable indirect calorimeter (Oxycon Mobile). Results: Playing Wii Boxing resulted in light intensity activity (2.46 METs) while playing Wii Fit Free Jogging resulted in moderate intensity physical activity (4.44 METs). No significant difference was seen between groups in the energy cost of playing active video games. Conclusion: Active video games are a useful source of light to moderate intensity physical activity in children with cystic fibrosis.
PUBLISHED
Keywords: Physical activity; Metabolic equivalent; Video games